Book of proceedings of the 1st Machakos University Annual International Conference - Machakos University (Machakos University Press, 2018)
Cognizant of the challenges and opportunities presented by the United Nations adoption of the Seventeen Sustainable Development Goals and the Government of Kenya’s Big Four Agenda: Manufacturing, Food and Nutrition security, Health and Housing, the conference further cascades the theme of the conference into five sub- themes: 1) Agriculture, Food Security, and Agribusiness for Community Transformation 2) Transformative Development through Language, Culture and Communication Technology 3) Innovative Approaches to Education and Training for Sustainable Development 4) Business and Innovative Approaches for Small and Medium Enterprise Development 5) Science, Technology, Engineering, Mathematics and Innovation for Industrial Transformation These sub-themes were crafted to embrace main drivers of sustainable development goals, namely: sharing knowledge through education; effective communication through technology; human explorations and imaginations through Science and Mathematics, sustainable, long-term growth and job creation through Small and Medium Enterprises and food for all through Agriculture and Food Security. All the sub-themes in the conference embrace innovation domains, as key driver in fast tracking economic growth based on knowledge. Innovation then must be treated as business critical in all sectors, for increased prosperity.